A Novel Intelligent Shore-to-Ship Power Supply System Using Collaborative Motor Control - Pan, Lin; Shao, Jingkai (Frontiers in Mechanical Engineering, 2020)
In this paper, a novel type of intelligent cable lifting device for shore-to-ship power connection systems is proposed. By analyzing the shortcomings of the commonly used lifting methods in inland ports, the structure and control circuit of the new cable lifting device are designed based on collaborative motor control. The reliability and effectiveness of the proposed control strategy are verified by establishing a mathematical model of the motor and through Simulink software simulation analysis. The cable lifting device can adjust the cable delivery position in inland ports. It can, at the same time, significantly reduce manual operation and improve the efficiency of shore-to-ship power connection operation at the port terminal.